ANALISIS PENGARUH PERTUMBUHAN RASIO-RASIO KEUANGAN, LABA BERSIH, DAN UKURAN PERUSAHAAN TERHADAP PREDIKSI PERTUMBUHAN LABA USAHA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - Susi Dwimulyani; Shirley Shirley (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
The objective of this research is to recognize influencies of financial ratios growth, net income growth, and companies' size growth in predicting operating profit growth for several period ahead. To predict the operating profit growth, 20 financial ratios which categorized into 5 constructs, net income, and companies' size are used. This study used secondary data from financial statement of 34 manufacturing companies which are listed on Jakarta Stock Exchange for period year 2002 to year 2004. These companies selected by purposive sampling technique. After data collected, it will be calculate and analyze with statistic test to get the result. Statistic test used 2 methods those are multivariate regression method to test the influences of the financial ratios growth, net income growth, and companies' size growth toward operating profit growth perdiction at individual level and Analysis of Moment Structures (AMOS) method which used to test the influences of financial ratios growth, net income growth, and companies' size growth toward operating profit growth prediction at constructs level. Multivariate regression analysis which done partially, resulted gross profit margin ratio growth, debt to asset ratio growth, and companies' size growth could be used to predict manufacturing companies' operating profit growth for 1 year ahead, and simultaneously, all independent variables significantly affect to manufacturing companies' operating profit growth prediction for 1 year ahead. Analysis of Moment Structures (AMOS) was resulting independent variables those significantly affect to manufacturing companies' operating profit growth prediction for 1 year ahead are profitability ratio growth, net income growth, and companies' size growth